Role of QseG membrane protein in beneficial enterobacterial interactions with plants and Mesorhizobia - Brígido, C (2021)
Membrane protein Quorum sensing G (QseG) positively interferes in the process of colonization and infection of enteric pathogens in animals. Its gene is located between qseE and qseF genes and is co-transcribed with the two-component system. Homologs of qseG gene, along with qseEF, are present in many Enterobacteriaceae; however, its role in nonpathogenic strains is still unknown. To fill this knowledge gap, we investigated the role of QseG protein of a plant-associated enterobacterium in the interactions with its legume host and in the benefits induced by this enterobacterium in the Mesorhizobium-chickpea symbiosis. Here, we show that Kosakonia sp. MH5 ΔqseG mutant was defective in internal root colonization and inoculation of chickpea seedlings with this mutant increased the expression of the defence-related gene CaRBOH-like in host roots. Furthermore, we show that invasion and a proper establishment within the roots and/or root nodules are essential for MH5 strain to be able to exert beneficial effects on the symbiotic Mesorhizobium-chickpea association under salinity. This study demonstrates, for the first time, that the role of QseG is transversal to pathogenic and nonpathogenic enterobacteria and is a step forward to better understanding the molecular bases of plant-bacteria interactions established between legume and beneficial endophytic enterobacteria.